Psidium guajava leaves decrease arthritic symptoms in adjuvant-induced arthritic rats - Baroroh, Hanif Nasiatul; Utami, Esti Dyah; Achmad, Anisyah (Universa Medicina, 2015)
BACKGROUND Guava is an herbal with proven antioxidant and anti-inflammatory properties. The aim of this study was to investigate the anti-arthritic activity of the ethanol extract of Psidium gujava leaves (EEPG) against complete Freundâ€™s adjuvant (CFA) induced arthritis in rats. METHODSAn experimental study was conducted on 40 male Wistar Sprague Dawley rats, which were divided into 5 groups. Each group was induced with 0.2 mL CFA (1 mg/mL) on day 1 and 0.1 CFA mL booster injection on day 5. Group I served as an arthritic control, group II received dexamethasone (6.75 mg.kg-1 orally), group III, IV and V received EEPG at oral doses of 250, 500, and 750 mg/kg BW, respectively, on days 14 to 28. Anti-arthritic activity was observed from the arthritis score, the paw circumference was measured on days 0, 1, 4, 8, 12, 16, 20, 24, and 28, the mobility score was determined on days 12 and 28, and the histolopathology of the knee joint was examined on day 29. RESULTSEthanol extract of Psidium guajava leaves significantly suppressed the swelling of the paws in chronic phase based on increasing of edema (%), while starting on day 20. EEPG at 250 mg/kg was most effective in significantly reducing arthritis scores (p<0.05). Histopathological examination showed repair of the knee joint synovial membrane and cartilage.Â CONCLUSIONSPsidium guajava leaf extract is effective in decreasing the inflammatory response and arthritic symptoms in rats with adjuvant-induced arthritis. Psidium guajava leaves can be developed into an alternative anti-arthritis treatment.